Аналіз ефективності алгоритмів компенсації канальних спотворень у SDR - Жуга, Ю. С. (ХНУРЕ, 2024)
This paper examines the effectiveness of channel compensation algorithms in SDR systems using QPSK modulation. SDR's adaptability makes it integral to modern telecom. The study employs GNU Radio simulations to analyze noise impact on QPSK signals. Results highlight the necessity for robust compensation methods, especially under high noise conditions, to maintain SDR system integrity.
Keywords: спотворення у SDR; QPSK modulation